Pediatric patient with both leukocyte adhesion deficiency II and bombay blood group - Yaman, Yeşim; Aydın, Sultan; Acıpayam, Can; Sarıbeyoğlu Tuğrul, Ebru; Genel, Ferah (Ferrata Storti Foundation, 2016)
[Abstract Not Available]
Keywords: Pediatri; Leukocyte; Bombay